2016
DOI: 10.1371/journal.pone.0162785
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine Injection during Strabismus Surgery Reduces Emergence Agitation without Increasing the Oculocardiac Reflex in Children: A Randomized Controlled Trial

Abstract: ObjectiveDexmedetomidine is known to reduce the incidence of emergence agitation, which is a common complication after inhalational anesthesia like sevoflurane or desflurane in children. However, the dose of dexmedetomidine used for this purpose is reported variously and the most effective dose is not known. In this study, we tried to find the most effective dose of dexmedetomidine to reduce the incidence of emergence agitation in children undergoing strabismus surgery without the complications like oculocardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 36 publications
0
58
0
Order By: Relevance
“…This may be explained by the fact that spontaneous pain after skin incision, determined by a visual analogue scale, decreased rapidly. 21 Dexmedetomidine is known to decrease anaesthetic requirements and to induce emergence sedation 20 without respiratory depression. Consequently, under the clinical setting of this study that a similar end-tidal concentration of sevoflurane was maintained in both block and remifentanil groups during surgery, simple elimination of post-operative pain did not affect the incidence of EA after sevoflurane anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be explained by the fact that spontaneous pain after skin incision, determined by a visual analogue scale, decreased rapidly. 21 Dexmedetomidine is known to decrease anaesthetic requirements and to induce emergence sedation 20 without respiratory depression. Consequently, under the clinical setting of this study that a similar end-tidal concentration of sevoflurane was maintained in both block and remifentanil groups during surgery, simple elimination of post-operative pain did not affect the incidence of EA after sevoflurane anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, dexmedetomidine, a selective a2-adrenergic receptor agonist, investigated widely for preventing EA, may be a promising drug. 21 Dexmedetomidine is known to decrease anaesthetic requirements and to induce emergence sedation 20 without respiratory depression. 22 There are some limitations to this study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, whether dexmedetomidine can reduce EA, PONV, and postoperative pain incidence in pediatric patients undergoing strabismus surgery remains unclear. Moreover, relevant studies, which have only used small sample populations, have reported conflicting results [11][12][13][14][15][16][17][18][19]. Thus, meta-analyses evaluating the safety and efficacy of dexmedetomidine in pediatric strabismus surgery are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that DEX can both decrease the incidence of desaturation and reduce the secretions. [31,32] …”
Section: Discussionmentioning
confidence: 99%